2020
DOI: 10.3390/rel11110596
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Educational Intervention to Teach Spiritual Care to Spanish Nursing Students

Abstract: Spirituality and spiritual care in professional nursing are conceptualised and recognised as fundamental components of holistic healthcare. Despite the acceptance of and interest in spiritual care, a lack of education and clinical training on the subject limits nurses’ ability to meet patients’ spiritual needs. Consequently, the aim of this study was to analyse the effectiveness of a training programme designed to teach the specific knowledge, attitudes and competencies necessary to provide spiritual care in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
7
0
4
Order By: Relevance
“…The first mixed method finding was the spiritual care subject transformed the participant's knowledge and practice of spiritual care so they viewed themselves more enabled to provide spiritual care competently within holistic care practice after completion of the spiritual care subject. Other studies (Fernández-Pascual et al, 2020;Scott Barss, 2020;Taylor et al, 2009) also found spiritual care teaching and learning activities also had an influence on knowledge and practice of spiritual care. The beneficial influence of spiritual care education in undergraduate nursing programs was noted regardless of the institutional environment the student was studying in, for instance whether the student was studying at a public or private, religious or nonreligious affiliated institution (Cooper & Chang, 2016;Garner et al, 2002;Taylor et al, 2009).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The first mixed method finding was the spiritual care subject transformed the participant's knowledge and practice of spiritual care so they viewed themselves more enabled to provide spiritual care competently within holistic care practice after completion of the spiritual care subject. Other studies (Fernández-Pascual et al, 2020;Scott Barss, 2020;Taylor et al, 2009) also found spiritual care teaching and learning activities also had an influence on knowledge and practice of spiritual care. The beneficial influence of spiritual care education in undergraduate nursing programs was noted regardless of the institutional environment the student was studying in, for instance whether the student was studying at a public or private, religious or nonreligious affiliated institution (Cooper & Chang, 2016;Garner et al, 2002;Taylor et al, 2009).…”
Section: Discussionmentioning
confidence: 85%
“…Spirituality has had a range of meanings ascribed, including existential viewpoints such as finding purpose and meaning in life (Fernández-Pascual et al, 2020; van Leeuwen et al, 2021), religious perspectives (Chew et al, 2016; Ozbasaran et al, 2011), and hope and support in suffering (McSherry & Jamieson, 2013; Melhem et al, 2016). Spiritual care also has a diversity of interpretations including support of the patient's religious beliefs and needs (McSherry et al, 2020) and developing a compassionate relationship with and sensitively listening to a patient (van Leeuwen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some Muslim countries, there has been a need for formal training of nurses in providing spiritual care to patients, especially those with cancer [15]. Fernández-Pascual MD, et al [16] state the need to adopt an adequate curriculum and on-the-job training in the Muslim health care system to increase the competence of nurses in providing spiritual care to patients.…”
Section: Stage Threementioning
confidence: 99%
“…Fuente: Adaptado de la declaración PRISMA para publicación de revisiones sistemáticas y meta análisis Desde el punto de vista metodológico, un porcentaje importante de los estudios usan un diseño de tipo cuasiexperimental sin grupo control y con muestras seleccionadas a conveniencia, con participación voluntaria lo que pudiera emplear un sesgo de selección en los resultados [19][20][21][22] . Otros estudios (n=5) presentan aleatorización con grupo control lo que indica resultados más sólidos respecto al efecto [23][24][25][26] .…”
Section: Figura 1 Flujograma Para La Selección E Inclusión De Los Est...unclassified